METHODS FOR DEVELOPING STUDENTS’ CREATIVE ABILITIES USING EDUTAINMENT TECHNOLOGIES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The integration of edutainment technologies in educational settings provides a dynamic approach to fostering students’ creative abilities. These technologies combine entertainment with educational content, thereby creating engaging and interactive learning experiences that stimulate cognitive, emotional, and social development. By incorporating elements like games, simulations, and multimedia, edutainment encourages active participation, problem-solving, and critical thinking. This process not only motivates students but also enhances their creativity by offering diverse tools for expression and exploration. Various edutainment platforms, such as educational apps, virtual reality, and gamified learning environments, allow students to experiment, make mistakes, and learn in a risk-free atmosphere. The use of these technologies aligns with modern pedagogical trends that emphasize personalized learning, collaboration, and skill development. This method helps students apply their knowledge in practical, real-world scenarios, improving their ability to innovate and think outside the box. In conclusion, the application of edutainment technologies is a promising approach for the development of creative abilities in students, making the learning process more effective, enjoyable, and future-oriented.